Regulation of CHK1 by mTOR contributes to the evasion of DNA damage barrier of cancer cells - Xinhui Zhou (Nature Portfolio, 2017)
Abstract Oncogenic transformation leads to dysregulated cell proliferation, nutrient deficiency, and hypoxia resulting in metabolic stress and increased DNA damage. In normal cells, such metabolic stress leads to inhibition of signaling through the mammalian Target of Rapamycin Complex 1 (mTORC1), reduction of protein translation, cell cycle arrest, and conservation of energy. In contrast, negative regulation of mTORC1 signaling by DNA damage is abrogated in many cancer cells, thus mTORC1 signaling remains active under microenvironmental conditions that potentially promote endogenous DNA damage. Here we report that mTORC1 signaling suppresses endogenous DNA damage and replication stress. Pharmacological inhibition of mTOR signaling resulted in phosphorylation of H2AX concomitant with the decrease of CHK1 levels both in cell culture and mouse rhadomyosarcoma xenografts. Further results demonstrated that mTORC1-S6K1 signaling controls transcription of CHK1 via Rb-E2F by upregulating cyclin D and E. Consistent with these results, downregulation of CHK1 by inhibition of mTOR kinase resulted in defects in the slow S phase progression following DNA damage. These results indicate that, under stressful conditions, maintained mTORC1 signaling in cancer cells promotes survival by suppressing endogenous DNA damage, and may control cell fate through the regulation of CHK1.